REVISITING THE CONTENT OF NON-SPECIFIC INFLAMMATORY PROCESS MARKERS AND 25-HYDROXYVITAMIN D IN THE BLOOD OF PREGNANT WOMEN OF HIGH INFECTIOUS RISK - Manasova, G.S.; Didenkul, N.V.; Kuzmin, N.V.; Shpak, I.V.; Zhovtenko, O.V. (World of Medicine and Biology, 2022)
Intrauterine infection continues to have a negative impact on perinatal indicators. The aim of the study was to compare the concentration of some markers of the inflammatory process and vitamin D in the blood of pregnant women with placental dysfunction against the background of high infection risk (56 women – a group I), as well as in healthy pregnant women (40 women – group II). Blood levels of procalcitonin, lactate, C-reactive protein and vitamin D were determined by ELISA. More than 60 % of pregnant women from the I-st group were carriers of CMV, HSV, and toxoplasmosis. The violation of the vaginal ecosystem was determined in them 5 times more often than in group II. The level of vitamin D in the I-st group was lower than in the comparison group (31.73±8.6 ng/ml and 43.38±11.20 ng/ml; U=502.5, P=0.00001), and the content of C-reactive protein (15 times), procalcitonin (3 times) and lactate (2.2 times) was greater than in the control group. Low blood levels of calcidiol are associated with high levels of inflammatory markers. It is possible that the correction of vitamin D status in the pre-gravid stage and from the early stages of pregnancy in women at high infectious risk can contribute to the improvement of perinatal outcomes.
Keywords: pregnancy; intrauterine infection; vitamin D; procalcitonin; lactate; C-reactive protein